The CARICOMP Network of Caribbean Marine Laboratories (1985–2007): History, Key Findings, and Lessons Learned - Cortés, Jorge; Oxenford, Hazel A.; van Tussenbroek, Brigitta I.; Jordán-Dahlgren, Eric; Cróquer, Aldo; Bastidas, Carolina; Ogden, John C. (Frontiers in Marine Science, 2019)
Caribbean Coastal Marine Productivity (CARICOMP) was a basin-wide cooperative, international network of marine laboratories established in 1985. Recognizing major trends of change in coastal ecosystems and the importance of the linkages among them, our goal was to monitor synoptically with standardized methods the physical environment and to document trends in measures of the structure and functioning of coral reefs, seagrasses and mangroves. Between 1985 and 1993, the CARICOMP Steering Committee established a data management center and wrote a methods manual. Marine laboratories joined the program by appointing a Site Director and signing an agreement specifying the cost sharing and responsibilities of the laboratory. With significant outside funding in 1992, the program became fully functional and ultimately more than 30 institutions in 21 Caribbean countries participated. Monitoring lasted from 1992 to 2007, spanning many technological advances including the internet, automated in situ data logging and remote sensing. Annual CARICOMP meetings, organized at a different laboratory each year, were essential in standardization of methods and maintaining interest. Open access to the data was a goal from the start, although the members imposed an embargo to allow time to publish major results. At some of the sites, monitoring continues to this day, generating among the longest coastal monitoring data sets in the Caribbean, and possibly in the world. Over time, multi-authored papers were prepared for the Proceedings of the International Coral Reef Symposia and other journals, and independent scientists drew on the open database for regional analyses of ecosystem trends. Recently, active members have written summary papers based on the monitoring data covering physical parameters, coral reefs, seagrasses, and mangroves. Overall, the data reveal major differences across the region and changing rates and trends showing the dynamism and vulnerability of coastal ecosystems. The longer the monitoring continues, the more valuable the dataset becomes as a tool to discern the underlying factors driving the structure and functioning of Caribbean coastal ecosystems. Several recent workshops have concluded that the need for regionally cooperative monitoring and research has never been greater.